2007
DOI: 10.3184/030823407x244850
|View full text |Cite
|
Sign up to set email alerts
|

One-pot Regioselective Synthesis of 2,9-Disubstituted Imidazo[1,2-a] Benzimidazoles from 2-Aminobenzimidazole and α-Tosyloxy Ketones

Abstract: One-pot regioselective synthesis in high yields of 2,9-disubstituted imidazo[1,2-a]benzimidazoles from 2-aminobenzimidazole and α-tosyloxy ketones is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The increase in C 0 also enhances the interaction between adsorbate molecules and the vacant sorption sites on the GAC and the surface functional groups. The rate of removal of P and NP was faster initially and NP was more readily adsorbed than P, showing higher affinity of NP towards AC [70]. For example, the AN removal efficiency decreased from 97.8 to 89.5% as the AN concentration was increased from 20 to 200 mg dm -3 [58] and similar trends was found for removal of phenols [70,73].…”
Section: Gac and Its Characterizationsupporting
confidence: 61%
See 1 more Smart Citation
“…The increase in C 0 also enhances the interaction between adsorbate molecules and the vacant sorption sites on the GAC and the surface functional groups. The rate of removal of P and NP was faster initially and NP was more readily adsorbed than P, showing higher affinity of NP towards AC [70]. For example, the AN removal efficiency decreased from 97.8 to 89.5% as the AN concentration was increased from 20 to 200 mg dm -3 [58] and similar trends was found for removal of phenols [70,73].…”
Section: Gac and Its Characterizationsupporting
confidence: 61%
“…Effect of GAC dosage (m) Figure 7 shows the AN, P, CP and NP removal efficiency as a function of GAC dosage with C 0 of 1 [70] reported that NP showed more adsorbability than P. Only 6 g dm -3 of AC dose was required in case of NP as against the 10 g dm -3 of AC dose to effect the same amount of P,…”
Section: Gac and Its Characterizationmentioning
confidence: 99%